Output-boundary regulation for nonlinear nonminimum-phase systems - Arom Boekfah (2018)
Copyright © 2016 by ASME. Exact output tracking requires preview information of the desired output for nonminimum-phase systems. For situations when preview information is not available, this article proposes an output-boundary regulation (OBR) approach that maintains the output-tracking error within prescribed bounds for nonlinear nonminimum-phase systems. OBR transitions the output-tracking error to zero whenever the output error reaches a set magnitude using polynomial output trajectories for each transition. The main contribution is to show that an output-transition-based OBR (O-OBR, which uses post-actuation input to transition the system state after the output-error transition is completed) can enable OBR of more aggressive output trajectories when compared to a state-transition-based OBR (S-OBR) that transitions the full system state and therefore achieves the output transition as well. Results from an example simulation system is used to illustrate the proposed OBR approach and comparatively evaluate the S-OBR and O-OBR approaches, which show that, for the example system, the O-OBR can track 3 times faster desired output trajectory than the S-OBR approach.